Analisis Kemampuan Metakognisi Siswa Dalam Memecahkan Masalah Matematika Pada Materi Barisan Dan Deret Aritmatia Kelas X SMK Bina Teknika - Patmah, Prianti; Siagian, Roida Eva Flora; Marliani, Novi (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to analyze the metacognitive abilities of students in solving mathematical problems in class X MPLB 3 SMK Bina Teknika using a descriptive qualitative approach.A total of 46 students were given a metacognitive ability questionnaire.Next, after classification, subjects with high, medium, and low metacognitive abilities were identified.The classified subjects were given a problemsolving test.The research results show that subjects with high metacognitive abilities have good problemsolving skills by fulfilling all the problem-solving steps.Next, subjects with moderate metacognitive ability had some problem-solving steps that were not fulfilled, and finally, subjects with low metacognitive ability only fulfilled the step of planning the problem-solving, which was planning the appropriate formula, but the other steps were not fulfilled.This research shows how metacognitive ability can play a role in solving mathematical problems.With metacognitive abilities, students can be aware of their own thinking processes, allowing them to determine which strategies to use in solving math problems.